Department of Land Resources and Environment, Faculty of Agriculture, Khon Kaen University, Khon Kaen 40002, Thailand - Pruksakorn, Chantima; Pimarn, Chakrabhandhu; Boonsoongnern, Alongkot; Narongsak, Watcharachai (Agriculture and Natural Resources, 2016)
The presence and characteristics were investigated of vancomycin-resistant enterococci (VRE) in pigs in Thailand. A total of 179 rectal swabs were collected aseptically from suckling pigs, fattening pigs and breeding sows on four commercial farms located in Central Thailand. VRE with minimum inhibitory concentrations ranging from 8 mg/mL to 16 mg/mL were detected in 43 of 179 pigs (an overall prevalence rate of 24%). VRE carriers were identified in 12 of 61 (19.7%) suckling pigs, 15 of 60 (25%) fattening pigs and 16 of 58 (27.6%) breeding sows, respectively. Enterococcus gallinarum was the most prevalent species for VRE in all age groups, followed by the detection of Enterococcus casseliflavus. All of the isolates were susceptible to teicoplanin. A large proportion of VRE isolates showed resistance to tetracycline (86.5%), erythromycin (61.5%), ampicillin (53.8%), chloramphenicol (34.6%) and ciprofloxacin (32.7%). Resistance to ampicillin was more prevalent in E. gallinarum isolates than in E. casseliflavus isolates. The results of this study indicate that VRE isolates of pigs are of the VanC phenotype and commonly exhibit multiple drug resistance. Different antimicrobial susceptibility is present between VanC species, while E. gallinarum is less susceptible than E. casseliflavus.